A microcomputer-based information management system for a nurse-managed clinic. - Pulliam L (Computers in Nursing)
A project team from a nurse-managed health care center designed and used a microcomputer-based information management system to document the activities of their clinic. Commercial software, dBase III Plus, was used to program the system, called Nurse Education Link to Aged Center (NELAC). NELAC reflects the center's philosophy of helping clients attain maximum satisfaction of their health care needs through self care. NELAC's specific purposes include 1) matching student nurses with potential clients for clinical experiences; 2) providing an efficient reminder system to improve follow-up care for clients; 3) maintaining longitudinal client records; 4) producing reports of services and activities of the center; and 5) providing aggregate data for research.